Hydrophilic and hydrophobic poly(l‐lactic acid) films by building porous topological surfaces. Issue 10 (3rd November 2016) - Sun, Hui; Wang, Yuanyuan; Zhang, Kaiyu; Zhong, Yonghui; Lin, Ligang; Zhou, Hao; Chen, Li; Zhang, Yuzhong
ABSTRACT: Surface wettability of thin films is significant for their functional properties. Poly(l ‐lactic acid) (PLLA) is proposed as film matrix for building porous topological surfaces. By controlling the dope composition and ambient conditions, the films with ordered pores at micrometer scale are obtained. The results demonstrate that the hydrophilic or hydrophobic surface can be realized by building the porous topological surfaces. Increasing polymer concentration can lead to decreased pore size. The transition behavior of surface pores from discrete bowl‐like to interconnected honeycomb‐like structure with the increasing humidity is observed. The contact angle of top surface of film is higher than that of bottom surface, which verified the different roughness performance. The morphology and scale of topological structure are markedly related with the template effect of water droplets. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 44572. Abstract :